E-health physical activity interventions and moderate-to-vigorous intensity physical activity levels among working-age women: a systematic review protocol - Reed, Jennifer L; Prince, Stephanie A; Cole, Christie A; Nerenberg, Kara A; Hiremath, Swapnil; Tulloch, Heather E; Fodor, J G; Szczotka, Agnieszka; McDonnell, Lisa A; Mullen, Kerri-Anne; Pipe, Andrew L; Reid, Robert D (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background The rapid pace of modern life requires working-age women to juggle occupational, family, and social demands. Despite the large numbers of working-age women in developed countries and the proven benefits of regular moderate-to-vigorous intensity aerobic physical activity (MVPA) in chronic disease prevention, few women meet current physical activity (PA) recommendations of 150 min of MVPA per week. It is important that appropriate and effective behavioral interventions targeting PA are identified and developed to improve the MVPA levels of working-age women. As women worldwide embrace modern technologies, e-health innovations may provide opportune and convenient methods of implementing programs and strategies to target PA in an effort to improve MVPA levels and cardiometabolic health. Previous reviews on this topic have been limited; none have focused on working-age women from developed countries who exhibit inappropriately low PA levels. It remains unknown as to which e-health interventions are most effective at increasing MVPA levels in this population. The purpose of this systematic review is to examine the effectiveness of e-health interventions in raising MVPA levels among working-age women in developed countries and to examine the effectiveness of these interventions in improving the health of women. Methods Eight electronic databases will be searched to identify all prospective cohort and experimental studies examining the impact of e-health interventions for increasing MVPA levels among working-age women (mean age 18–65 years) in developed countries. Gray literature including theses, dissertations, and government reports will also be examined. Study quality will be assessed using a modified Downs and Black checklist, and risk of bias will be assessed within and across all included studies using the Cochrane’s risk of bias tool and Grades of Recommendation, Assessment, Development and Evaluation approach. A quantitative synthesis in the form of meta-analyses for measures of MVPA and health outcomes will be conducted where possible. Discussion This review will determine the effectiveness of e-health interventions in raising MVPA levels in working-age women in developed countries. It will form a contemporary, rigorously developed, and reliable research base for policy makers and stakeholders; and inform and influence the development and implementation of effective e-health interventions designed to increase MVPA levels and improve health outcomes in this population. Systematic review registration PROSPERO CRD42014009534